Legal sanctity of consent for surgical procedures in India - Gauri Sharma; Vivek Tandon; P. Sarat Chandra (Indian Journal of Neurosurgery)
As surgeons, we are morally committed to respecting the right of self-determination of patients, thus an informed consent is necessary before any operative intervention. Many neurosurgical patients are incapable of giving consent because of impaired consciousness. Moreover, neurosurgical procedures involve high risks and often are time sensitive; therefore obtaining consent is a challenging job. Patients and their family members need immense courage, understanding, and trust before giving consent for a surgical procedure to a doctor. Lawsuits against doctors are on the rise and it is important to understand “what is consent?” in legal parlance.